Tugboat Clearance SOP Enhancement for Maritime Port Service Quality - Brenhard Mangatur Tampubolon; Larsen Barasa; Aji Permana; Nurul Wahyuni; Jaja Suparman (Harmony Management: International Journal of Management Science and Business, 2025)
This qualitative study examines standard operating procedure (SOP) implementation for tugboat clearance operations at Jepara Port, analyzing service quality enhancement through comprehensive stakeholder engagement. Utilizing semi-structured interviews with 25 participants across five stakeholder categories, the research reveals significant operational improvements including a 35% reduction in clearance processing times and a 35.5% increase in stakeholder satisfaction scores. Findings demonstrate that standardized procedures enhance port operational efficiency while strengthening maritime vocational education integration. Beyond efficiency gains, the study highlights the role of SOPs in ensuring transparency, accountability, and consistency in port service delivery. Respondents emphasized that clear procedural guidelines reduce uncertainty, minimize conflicts between stakeholders, and establish a common framework for decision-making in dynamic operational contexts. Moreover, the integration of vocational education elements into procedural design strengthens workforce competencies, aligning training curricula with real-world port requirements and industry expectations. The study contributes both theoretically and practically by offering evidence-based frameworks that can be adopted by other Indonesian ports. It underscores the importance of combining procedural standardization with stakeholder collaboration to achieve sustainable improvements in maritime service quality. Overall, the findings establish replicable models for enhancing national port competitiveness and advancing maritime industry development through systematic procedural and operational innovation that ensures long-term sustainability and resilience.